10.1016/s1553-3212(12)70211-x (CrossRef Listing of Deleted DOIs, 2000)
Trichotillomania (TTM) has shown high rates of comorbidity with ADHD. While both disorders have been associated with some performance deficits on measures of motor response inhibition, findings on deficits in TTM have been mixed. Deficits previously found in TTM may be in part a reflection of the presence of comorbid ADHD in the TTM subsamples. We compared adults with self-reported TTM alone (n = 59) and those with self-reported TTM and ADHD (n = 61) to a healthy control group (n = 59) on two response inhibition measures, the Go/No-Go task and the Stop Signal Task. We hypothesized that those with comorbid TTM and ADHD would have impaired performance relative to TTM alone and healthy controls, while TTM alone would not differ from controls, but our results showed nonsignificant differences among the three groups. These results did not support the idea that self-reported comorbid ADHD could explain variable TTM performance on motor response inhibition tasks.